MISOPROSTOL FOR THE PURPOSE OF MID-TRIMESTER TERMINATION OF PREGNANCY: A COMPARATIVE STUDY WITH PROSTAGLANDIN F2 ALPHA - Imran, Faiqa; Anser, Afia; Danish, Nargis; Fatima, Naheed (Journal of Ayub Medical College Abbottabad, 2010)
Objective: To compare the efficacy of misoprostol verses prostaglandin F2Î± (PGF2Î±) in the medical management of termination of mid-trimester pregnancy due to medical reasons. Methods: This experimental study was conducted in Obstetrics and Gynaecology Department, Bahawal Victoria Hospital, Bahawalpur for a period of 6 months from April 2005 to September 2005. Time interval between induction with misoprostol or PGF2Î± and expulsion of foetus, number of tablets of misoprostol used and total dose of injection PGF2Î± used for termination of pregnancy as well as the complications experienced with both drugs. Fifty patients of 18-35 years of age were randomly selected who presented to Gynaecology and Obstetrics outdoor with mid-trimester foetal loss or congenitally malformed foetus incompatible to life, confirmed on ultrasonography. These women were randomised to receive either intravaginal misoprostol or extra-amniotic PGF2Î±. Results: Ninety-six percent of cases were managed successfully with Misoprostol as compared to 92% where PGF2Î± was tried (p>0.5). Mean induction to expulsion duration for misoprostol and PGF2Î± were 9.02±4.57 and 16.04±6.22 hours respectively (p<0.5). Complications profile was low especially in cases of PGF2Î± and only one case experienced significant haemorrhage. Conclusion: Misoprostol and PGF2Î± were found to be of same success rate but former was found to be more efficacious in terms of induction to expulsion duration. Keywords: Misoprostol, Mid-trimester foetal death, PGF2Î±, Abortion, Pregnancy, Outcome, Second trimester termination of pregnancy